Legal Analysis of Engagement for Tax Interpretation in Leasing and Service Provision - Sumiyati Sumiyati (International Journal Labs, 2022)
This study aims to: (1) To determine whether the application of Civil Law has been carried out in the Application of Tax Law. (2) To find out the interpretation of Civil Law in terms of rental agreements and service delivery in taxation. dassain and dassolen in this study used primary data and secondary data obtained from the field. Based on the Supreme Court Decision Number 425/B/PK/PJK/2012 The results of this study indicate that; (1) Tax law is a part of public law that regulates the relationship between the government (Fiskus) as a tax collector and the community, namely the taxpayers. Tax law adheres to the principle of taxation if two conditions are met, namely objective conditions and subjective conditions. Both objective terms and subjective conditions are closely related to the provisions of civil law. The following is a discussion of the relationship between tax law and civil law in terms of objective and subjective terms (2) Judge's interpretation in this tax dispute, PT Cotrans Asia proposes several arguments based on the agreement made by PT Cotrans Asia interpretation of Civil Law in terms of rental and delivery agreements services in taxation. Judge's Decision In Supreme Court's Decision No. 425/B/PK/PJK/2012 The Panel of Judges is of the opinion that the reasons for the review cannot be justified due to legal considerations and the Tax Court's Decision which rejected the appeal of the Appellant against the Decision of the Director General of Taxes Number KEP-59/PJ.07/2009 dated February 16, 2009 regarding the objection to the underpayment of income tax assessment letter Article 23 for the March to October 2007 tax period Number 00001/203/07/725/07 dated 11 December 2007 on behalf of PT Cotrans Asia is correct and correct in accordance with the provisions of the regulations current regulation. Based on the results of the study, it is recommended; (1) DGT should use the Law of Engagement as the main basis to see the application of Tax Law, including in the classification of income, for example to determine whether the income given is rental income or service income by looking at the agreement made and also using Civil Law as a reference. DGT also needs to make laws or laws that are binding in the application of Tax Law in terms of the delivery of services based on an agreement, for example on the delivery of shipping services that will use the basis of the Shipping Law in the delivery of shipping services. -The government, in this case the Directorate General of Taxes, must make further provisions regarding lex specialist in terms of the Law of Engagement which is the basis for the application of Tax Law in Indonesia, not only for the application of tax rules for leasing but also for the delivery of services. In general, provisions need to be made. in detail about how the application of the principle of lex specialist in Tax Law compared to other laws in a civil manner. (2) needs to be done -Socialization among the tax authorities or tax officers needs to be done regarding the application of Civil Law in relation to the application of Tax Law